Forensic science in the justice system: learnings from the Queensland DNA inquiry - Walvisch, Jamie; Kogios, Rebecca; Davey, Anna (Australian journal of forensic sciences, 2025)
The Queensland DNA Inquiry, conducted by Walter Sofronoff KC, unearthed substantial deficiencies in forensic DNA practices, highlighting the need for rigorous scientific standards and improved management within forensic laboratories. The inquiry's final report made 123 recommendations to overhaul these practices, prompting the Queensland Government to pledge over $95 million towards restructuring forensic services. This paper reflects on a workshop convened by the Victorian Chapter of the Australian Academy of Forensic Sciences, which explored the implications of these recommendations for other jurisdictions. The workshop facilitated a rich dialogue among legal, scientific, and government sectors, emphasizing the necessity of a holistic approach to forensic science within the justice system. It underscored the importance of impartiality in forensic services, the need for fit-for-purpose operational frameworks, and robust quality management to uphold the integrity of forensic evidence. By examining these themes, the paper contributes to ongoing discussions about enhancing forensic science's role in ensuring justice and underscores the potential for significant reforms catalysed by the inquiry's findings.